Polyphenols: Immunomodulatory and Therapeutic Implication in Colorectal Cancer - Mileo, Anna Maria; Nisticò, Paola; Miccadei, Stefania (Frontiers in Immunology, 2019)
Polyphenolic compounds, widely present in fruits, vegetables and cereals, have potential benefits for human health and are protective agents against the development of chronic/degenerative diseases including cancer. More recently these bioactive molecules have been gaining great interest as anti-inflammatory and immunomodulatory agents, mainly in neoplasia where the pro-inflammatory context might promote carcinogenesis. Colorectal cancer (CRC) is considered a major public healthy issue, a leading cause of cancer mortality and morbidity worldwide. Epidemiological, pre-clinical and clinical investigations have consistently highlighted important relationships between large bowel inflammation, gut microbiota (GM) and colon carcinogenesis. Many experimental studies and clinical evidence suggest that polyphenols have a relevant role in CRC chemoprevention, exhibit cytotoxic capability versus CRC cells and induce increased sensitization to chemo/radiotherapies. These effects are most likely related to the immunomodulatory properties of polyphenols able to modulate cytokine and chemokine production and activation of immune cells. In this review we summarize recent advancements on immunomodulatory activities of polyphenols and their ability to counteract the inflammatory tumor microenvironment. We focus on potential role of natural polyphenols in increasing the cell sensitivity to colon cancer therapies, highlighting the polyphenol-based combined treatments as innovative immunomodulatory strategies to inhibit the growth of CRC.